Antiphospholipid syndrome presenting as progressive neuropsychiatric disorders: two case reports - Li CH; Chou MC; Liu CK; Lai CL (Neuropsychiatric Disease and Treatment, 2013)
Chien-Hsun Li,1–3 Mei-Chuan Chou,2,4 Ching-Kuan Liu,2,3 Chiou-Lian Lai2,31Department of Neurology, Fooyin University Hospital, Pingtung, Taiwan; 2Department of Neurology, Kaohsiung Medical University Hospital, Kaohsiung, Taiwan; 3Department of and Master’s Program in Neurology, School of Medicine, College of Medicine, Kaohsiung Medical University, Kaohsiung, Taiwan; 4Department of Neurology, Kaohsiung Municipal Ta-Tung Hospital, Kaohsiung, TaiwanAbstract: The antiphospholipid syndrome (APS) is a rare form of autoimmune coagulopathy. In this syndrome, the most common neurologic abnormality is transient ischemic attack. This can be easily overlooked if a patient presents with progressive neuropsychiatric disorders, such as depression or dementia. We report two cases of young women, aged 35 and 22 years, presenting with progressive depression and mental decline over a certain period. The neuropsychological diagnoses of the two patients were, respectively, dementia with disinhibition and borderline dementia with depression. Brain magnetic resonance imaging showed multiple old infarcts with encephalomalacia in the former case, and only one cortical hemorrhagic infarction, over the right temporoparietal lobe, observed in the latter case. The outcomes of the two cases were also very different. Progressive neuropsychiatric disorders are increasingly observed in the young; therefore, APS and other autoimmune diseases should be considered during the differential diagnosis. Brain imaging examinations may prevent a delay in the detection of a structural lesion and facilitate the early intervention with good prognosis. Careful investigations by experts from different disciplines are always encouraged in complicated cases.Keywords: autoimmune disease, brain imaging, dementia, depression, cerebrovascular disease